Evaluation of CRISPR/Cas9 site-specific function and validation of sgRNA sequence by a Cas9/sgRNA-assisted reverse PCR technique - Zhang, Beibei (Anal Bioanal Chem, 2021)
The effective application of the clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 system in biology, medicine and other fields is hindered by the off-target effects and loci-affinity of Cas9-sgRNA, especially at a genome-wide scale. In order to eliminate the occurrence of off-target effects and evaluate loci-affinity by CRISPR/Cas9 site-specific detection and screening of high-affinity sgRNA sequences, respectively, we develop a CRISPR/Cas9-assisted reverse PCR method for site-specific detection and sgRNA sequence validation. The detection method based on PCR can be used directly in the laboratory with PCR reaction conditions, without the need for an additional detection system, and the whole process of detection can be completed within 2 h. Therefore, it can be easily popularized with a PCR instrument. Finally, this method is fully verified by detecting multiple forms of site mutations and evaluating the affinity of a variety of sgRNA sequences for the CRISPR/Cas9 system. In sum, it provides an effective new analysis tool for CRISPR/Cas9 genome editing-related research. GRAPHICAL ABSTRACT: [Figure: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00216-021-03173-2.